Transcriptome profile of halofuginone resistant and sensitive strains of Eimeria tenella - Sun, Pei; Wang, Chaoyue; Zhang, Yuanyuan; Tang, Xinming; Hu, Dandan; Xie, Fujie; Hao, Zhenkai; Suo, Jingxia; Yu, Yonglan; Suo, Xun; Liu, Xianyong (Frontiers in Microbiology, 2023)
The antiparasitic drug halofuginone is important for controlling apicomplexan parasites. However, the occurrence of halofuginone resistance is a major obstacle for it to the treatment of apicomplexan parasites. Current studies have identified the molecular marker and drug resistance mechanisms of halofuginone in Plasmodium falciparum. In this study, we tried to use transcriptomic data to explore resistance mechanisms of halofuginone in apicomplexan parasites of the genus Eimeria (Apicomplexa: Eimeriidae). After halofuginone treatment of E. tenella parasites, transcriptome analysis was performed using samples derived from both resistant and sensitive strains. In the sensitive group, DEGs associated with enzymes were significantly downregulated, whereas the DNA damaging process was upregulated after halofuginone treatment, revealing the mechanism of halofuginone-induced parasite death. In addition, 1,325 differentially expressed genes (DEGs) were detected between halofuginone resistant and sensitive strains, and the DEGs related to translation were significantly downregulated after halofuginone induction. Overall, our results provide a gene expression profile for further studies on the mechanism of halofuginone resistance in E. tenella.